MALIGNANT MELANOMA OF ORAL CAVITY - Bajpai, Manas; Pardhe, Nilesh; Chandolia, Betina (Journal of Ayub Medical College Abbottabad, 2017)
A 51 year old male presented to the Department of Oral and Maxillofacial Pathology, NIMS Dental College Jaipur (India) with a painless pigmented patch extending from left side of the palate to the gingiva from 9 months. The patient had noticed the growth 7 months ago; it was a small patch of 1 cm initially, which gradually increased to attain the present size. The lesion was completely asymptomatic without any ulceration and mobility of the teeth.